1981
DOI: 10.1128/iai.33.3.958-961.1981
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive ribonucleic acid patterns of human rotavirus subgroups 1 and 2

Abstract: The ribonucleic acid migration patterns of 7 subgroup 1 and 16 subgroup 2 human rotaviruses recovered from four geographic areas were compared. The subgroup 1 ribonucleic acid patterns had strikingly slower-moving segments 10 and 11, suggesting a correlation between the ribonucleic acid pattern and the subgroup specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
63
2

Year Published

1982
1982
1990
1990

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(73 citation statements)
references
References 10 publications
8
63
2
Order By: Relevance
“…Eight different profiles were observed and all were typical for Group A rotaviruses (Pedley et al, 1983), except for the C7 type which was typified by the lack of a band in the Segment 11 region and the appearance of a band between Segments 6 and 7. Variation in the position of Segment 11 has been reported for Subgroups 1 and 2 of human Group A rotaviruses (Kalica et al, 1981), although not to the extent seen with the C7 isolates. Rotaviruses with unusual genome profiles have been detected in man and animals (Pedley et al, 1983;Snodgrass et al, 1984), but these isolates have distinct group antigens and their genome profiles lack a triplet of Segments 7, 8 and 9, having similar electrophoretic mobilities, characteristic of Group A viruses.…”
Section: Discussionmentioning
confidence: 93%
“…Eight different profiles were observed and all were typical for Group A rotaviruses (Pedley et al, 1983), except for the C7 type which was typified by the lack of a band in the Segment 11 region and the appearance of a band between Segments 6 and 7. Variation in the position of Segment 11 has been reported for Subgroups 1 and 2 of human Group A rotaviruses (Kalica et al, 1981), although not to the extent seen with the C7 isolates. Rotaviruses with unusual genome profiles have been detected in man and animals (Pedley et al, 1983;Snodgrass et al, 1984), but these isolates have distinct group antigens and their genome profiles lack a triplet of Segments 7, 8 and 9, having similar electrophoretic mobilities, characteristic of Group A viruses.…”
Section: Discussionmentioning
confidence: 93%
“…However, there is no genetic base for this correlation [Garbarg-Chenon et al, 1986;Urasawa et al, 19861. In addition to the two antigenic specificities, subgroup and serotype, which are assigned to the gene products of either RNA segment 6 or of segment 9 (or 8) Kalica et al, 1981;Chanock et al, 19831, there is evidence that Vp3, the product of the 4th gene, has an antigenic specificity involved in the neutralization of rotavirus infectivity [Hoshino et al, 19851. So far, only one HRV strain detected under natural conditions has been reported to have unusual features conflicting with the above rules; a strain called 82A001 with a "long" RNA pattern belonged to subgroup I [Nakagomi et al, 19851. This HRV strain was propagated in tissue culture, designated as AU-1 and confirmed as having unusual genetic and serological features.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of differences in the migration of RNA segments on gels, Espejo et al have demonstrated the presence of two distinct RNA patterns among human rotaviruses obtained from different epidemics (1)(2)(3)(4)(5). Most recently, the existence of a correlation between the RNA patterns of human rotaviruses and their serotypes (subgroups) has been demonstrated (6).…”
mentioning
confidence: 99%
“…In collaboration with Dr. A.Z. Kapikian and his colleagues (National Institutes of Health, Bethesda, U.S.A.), 11 rotavirus strains with various RNA patterns were serotyped by the enzyme-linked immunosorbent assay (ELISA) and immune adherence hemagglutination (IAHA) (6,7). The results showed that all the viruses with an RNA pattern of the 8 type should be classified as subgroup I and the viruses with RNA pattern of the L type as subgroup 2 (Table I).…”
mentioning
confidence: 99%